Effect of Co, Ti and Cr Additions on Microstructure, Magnetic Properties and Corrosion Resistance of Magnetocaloric Gd-Ge-Si Alloys - Hasiak, Mariusz (Materials (Basel), 2020)
The paper presents studies of microstructure, magnetic and corrosion properties of the Gd(58)Ge(20)Si(22), Gd(56)Ge(20)Si(22)Co(2), Gd(56)Ge(20)Si(22)Ti(2) and Gd(56)Ge(20)Si(22)Cr(2) (at.%) alloys after isothermal heat treatment at 1450 K for 2 h. The structure investigations of the produced materials performed by X-ray diffraction show the presence of Gd(5)Ge(2)Si(2)-type phase in all investigated samples. DC and AC magnetic measurements confirmed that the Curie temperature depends on the chemical composition of the produced alloys. From M(T) characteristics, it was found that the lowest Curie point (T(C) = 268 K) was estimated for the Gd(58)Ge(20)Si(22) sample, whereas the highest value of the Curie temperature (T(C) = 308 K) was for the Gd(56)Ge(20)Si(22)Cr(2) alloys. Moreover, the GdGeSi alloy without alloying additions shows the highest magnetic entropy change |ΔS(M)| = 15.07 J⋅kg(−1)⋅K(−1) for the maximum magnetic field of 2 T. The maximum |ΔS(M)| measured for the Gd(56)Ge(20)Si(22) with the addition of Co, Ti or Cr for the same magnetic field was obtained in the vicinity of the Curie point and equals to 2.92, 2.73 and 2.95 J⋅kg(−1)⋅K(−1), respectively. Electrochemical studies of the produced materials for 60 min and 55 days exposure in 3% NaCl solution show that the highest stability and corrosion resistance were exhibited the sample with added of Ti.